2012
DOI: 10.5433/1679-0359.2012v33n3p1209
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos qualitativos da silagem de capim-elefante com fubá de milho e casca de soja

Abstract: Objetivou-se com este trabalho, avaliar os efeitos do fubá de milho e da casca de soja na silagem de Pennisetum purpureum cv. Roxo Botucatu. Utilizou-se um delineamento inteiramente casualizado, em esquema de parcela subdividida, com sete tratamentos (capim-elefante puro, casca de soja (5 e 10%) e fubá de milho (5 e 10%) de forma isolada ou conjunta em mesmas proporções totalizando 5 e 10%), três tempos de abertura e três repetições. Foram utilizados silos experimentais constituídos de baldes plásticos de 20 L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 8 publications
2
16
1
7
Order By: Relevance
“…The Tifton 85 bermudagrass grass silage plus soybean hulls had higher levels of DM (38.75 g kg -1 ) followed by Tifton 85 bermudagrass plus corn grits keeping the same trend obtained before ensiling. Andrade et al (2012) obtained with the addition of 100g kg -1 of soybean hulls and corn meal, increases of 340 and 370 g kg -1 DM in the elephant grass silage with 80 days of regrowth compared to elephant grass silage without additives, showing in this essay that the corn meal showed higher absorbency compared to corn grits which was used in this test.…”
Section: Resultsmentioning
confidence: 86%
“…The Tifton 85 bermudagrass grass silage plus soybean hulls had higher levels of DM (38.75 g kg -1 ) followed by Tifton 85 bermudagrass plus corn grits keeping the same trend obtained before ensiling. Andrade et al (2012) obtained with the addition of 100g kg -1 of soybean hulls and corn meal, increases of 340 and 370 g kg -1 DM in the elephant grass silage with 80 days of regrowth compared to elephant grass silage without additives, showing in this essay that the corn meal showed higher absorbency compared to corn grits which was used in this test.…”
Section: Resultsmentioning
confidence: 86%
“…According to Andrade et al (2012), titratable acidity is a sensitive indicator that, along with pH, should be used in the evaluation of silage fermentation. These results corroborate the recommendations in the literature, as works carried out by Figueredo et al (2014) showed this relationship.…”
Section: Resultsmentioning
confidence: 99%
“…Estes resultados estão de acordo com os encontrados por AndrAde et al (2012), que utilizaram casca de soja e fubá de milho como aditivos na silagem de capim elefante e também observaram que a silagem sem aditivos apresentou menor teor de matéria seca.…”
Section: Resultsunclassified